ReAttach Therapy as a Component of a Multidisciplinary Approach to Dental Care for Children with Autism - A Narrative Review - Ganesh Kulkarni, Suchitra Gorle, Smitha Shetty, Neelam Vijayawargiya, Triveni Patil, Veena Kalburgi (Journal for ReAttach Therapy and Developmental Diversities, 2023)
This review explores the integration of ReAttach Therapy as a pivotal component within a multidisciplinary approach to dental care for children with Autism Spectrum Disorder (ASD). Children with ASD often face unique challenges in maintaining oral health due to sensory sensitivities, communication difficulties, and behavioral traits. Recognizing the significance of oral care in their overall well-being, healthcare professionals are increasingly adopting multidisciplinary approaches to address these challenges comprehensively. ReAttach Therapy, an emerging therapeutic approach, offers promise in enhancing the social and communication skills of children with ASD, making it particularly relevant to the dental care context. This review introduces ReAttach Therapy, elucidates its principles, techniques, and goals, and summarizes existing research on its effectiveness in improving social and communication skills in children with ASD. It also explores how ReAttach Therapy can be seamlessly integrated into a comprehensive dental care plan for children with ASD, enhancing their overall dental care experience and outcomes. By combining the expertise of dentists, pediatricians, speech therapists, occupational therapists, psychologists, and ReAttach therapists, this multidisciplinary approach aims to provide patient-centered care that addresses the multifaceted needs of children with ASD, ultimately promoting optimal oral health and quality of life.